The Influence of Work Environment and Leadership Style on Employee Job Satisfaction at PT Indosato Jaya Makmur - Kelvin Pangestu; Joko Ariawan (Journal of Current Research In Multidisciplinary, 2023)
This research was conducted to determine the influence of the work environment and leadership style on job satisfaction and aims to analyze how much influence the work environment and leadership style partially, jointly, or simultaneously have on employee job satisfaction. This research uses an observational method with a quantitative approach by distributing questionnaires to the entire research sample of 69 employees. The results of the work environment t-test research on job satisfaction were based on t-count results of 4.769 > t-table 1.996 and on leadership style t-tests on job satisfaction with t-count results of 2.818 > 1.996. So it can be concluded that work environment variables and leadership style have a significant, partial, or simultaneous effect on employee performance. By further improving the comfort of the work environment and a good leadership style, it will have a positive effect on employee job satisfaction.